Dual-Task nTMS Mapping to Visualize the Cortico-Subcortical Language Network and Capture Postoperative Outcome—A Patient Series in Neurosurgery - Ohlerth, Ann-Katrin; Bastiaanse, Roelien; Nickels, Lyndsey; Neu, Beate; Zhang, Wei; Ille, Sebastian; Sollmann, Nico; Krieg, Sandro M. (Frontiers in Oncology, 2022)
Background: Perioperative assessment of language function in brain tumor patients commonly relies on administration of object naming during stimulation mapping. Ample research, however, points to the benefit of adding verb tasks to the testing paradigm in order to delineate and preserve postoperative language function more comprehensively. This research uses a case series approach to explore the feasibility and added value of a dual-task protocol that includes both a noun task (object naming) and a verb task (action naming) in perioperative delineation of language functions. Materials and Methods: Seven neurosurgical cases underwent perioperative language assessment with both object and action naming. This entailed preoperative baseline testing, preoperative stimulation mapping with navigated Transcranial Magnetic Stimulation (nTMS) with subsequent white matter visualization, intraoperative mapping with Direct Electrical Stimulation (DES) in 4 cases, and postoperative imaging and examination of language change. Results: We observed a divergent pattern of language organization and decline between cases who showed lesions close to the delineated language network and hence underwent DES mapping, and those that did not. The latter displayed no new impairment postoperatively consistent with an unharmed network for the neural circuits of both object and action naming. For the cases who underwent DES, on the other hand, a higher sensitivity was found for action naming over object naming. Firstly, action naming preferentially predicted the overall language state compared to aphasia batteries. Secondly, it more accurately predicted intraoperative positive language areas as revealed by DES. Thirdly, double dissociations between postoperatively unimpaired object naming and impaired action naming and vice versa indicate segregated skills and neural representation for noun versus verb processing, especially in the ventral stream. Overlaying postoperative imaging with object and action naming networks revealed that dual-task nTMS mapping can explain the drop in performance in those cases where the network appeared in proximity to the resection cavity. Conclusion: Using a dual-task protocol for visualization of cortical and subcortical language areas through nTMS mapping proved to be able to capture network-to-deficit relations in our case series. Ultimately, adding action naming to clinical nTMS and DES mapping may help prevent postoperative deficits of this seemingly segregated skill.